COSTING SYSTEMS USED IN METALMECHANICAL COMPANIES ON THE EASTERN COAST OF LAKE MARACAIBO - Castro Albornoz, Juan (Revista Arbitrada Formación Gerencial, 2024)
This writing determines which costing systems are used by the studied 46 metalworking companies on the East Coast of the Maracaibo Lake (COL), through casual or incidental sampling (Parra, 2000, p. 21). This research determined that all metalworking companies must provide their customers, cost structures that involve all regular or routine items, which resemble total costing systems; however, all companies use partial absorption costing system, consistent with IASB-2, to specify the cost of sales indicated in the statement of income. However, almost all companies use the cost system of the organic law of fair prices in their customers’ quotes. Costing systems are considered to be main information systems to manage the cost objects, such as products, processes, departments and activities, which in turn allows to get an add value which promotes the company’s profitability through cost management however, the 6.44% of the metalworking companies, use cost information to the purposes outlined above.